Using multi-layer structure to improve the radiative cooling performance. (August 2020) - Fan, Xiaochun; Shi, Kailiang; Xia, Zhilin
Highlights: A multi-layer cooler structure has been proposed to improve the radiative cooling ability. This multi-layer structure has experimentally achieved 16% improvement compared with the usually used single-layer cooler. Abstract: Radiative cooling is a new method to passively cool object without consuming any energy. Recent study on radiative cooling has gained a lot of progress. However, the cooling ability of radiative cooler is limited due to non-radiative heat loss. In this study, we proposed a novel multi-layer cooler structure to improve the radiative cooling performance and experimentally demonstrated a 16% improvement compared to the usually used single-layer cooler. This work indicates the potential application for multi-layer structure and suggests a new idea for improving the radiative cooling ability.